Religious Architecture in the Achaemenid Capitals - Abdulhadi Barghash, Sa'doon; Abbas Fadhal , Ahmed (Journal of College of Education, 2021)
This research discusses the most important monuments left by the Persian Empire in relation to religious architecture. This study aims at shedding light upon the most prominent religious buildings in the capitals of the Achaemenid. This research also includes a collection of royal tombs and temples, such as: The Propylaeum, the Central Temple or the Mosalla, the Altars of the Fire, the Holy Temple, the Terraced Hill, the Stone Tower, in addition to the Square Temple.